OPTIMALISASI MEDIA SOSIAL INSTAGRAM SEBAGAI PENGEMBANGAN USAHA PADA UMKM KZ STORE SURABAYA - Shanti Septiana Rachmasari; Ugy Soebiantoro (POLITEKNIK PIKSI GANESHA, 2024)
In today's digital era, social media has become an inseparable part of daily life in society. In the business field, social media is one of the most effective tools for expanding reach and promoting businesses. KZ (Kaos dan Konveksi Zindy) Store Surabaya is an UMKM focused on producing textile products such as t-shirts, jackets, training outfits, sportswear, gamis, and shirts, along with other fashion products. KZ Store Surabaya aims to expand its market reach and build brand awareness by optimizing Instagram, the second most popular social media platform in Indonesia. The objective of this study is to optimize Instagram for business development at KZ Store Surabaya. The method used is qualitative, including observation, documentation, and interviews. The results show that optimizing Instagram for KZ Store Surabaya successfully expanded audience reach, built brand awareness, and increased audience interaction. Kata kunci : Social Media, Instagram, UMKM